Advancing synergistic strategies for greenhouse gas and atmospheric pollutant emission reduction in urban transportation: a whole lifecycle perspective - Sheng, Guojun; Sun, Zhiyuan; Xue, Mingyue; Sun, Dongshi; Xie, Danlan (Frontiers in Environmental Science, 2025)
In light of the interrelated origins and processes of greenhouse gas (GHG) and atmospheric pollutant emissions, countries around the world are actively seeking synergistic strategies for their reduction. Urban transportation represents a critical sector for GHG and air pollutant emissions; however, the effectiveness of existing collaborative measures has proven inadequate. This ineffectiveness primarily stems from a focus on terminal emission reductions, neglecting potential pollutant emissions that arise during implementation. To address this gap, this paper develops seven scenarios for coordinated emission reductions in urban transportation and employs econometric methods to quantitatively assess the effectiveness of these strategies throughout their entire lifecycle. Furthermore, the evaluation integrates key indicators, such as synergistic emission reduction, a coordinated control system, and cross-elasticity, to provide a comprehensive analysis of the proposed measures. This paper uses Shenyang, China, as a case study, revealing that enhancing fuel quality emerges as the most critical strategy for synergistic emission reduction. Although the comprehensive synergistic emission reductions associated with rail transit and low-carbon travel are not the highest, they demonstrate a significant linkage effect. Although the promotion of new energy vehicles (NEVs) offers substantial terminal emission reductions, their energy generation processes and consumption during charging classify them as non-synergistic measures. This study addresses the prevalent issue of overemphasizing terminal governance, providing valuable insights for policymakers in the urban transportation sector. It facilitates a deeper understanding of the synergistic control characteristics of various measures, enabling the identification of effective strategies and the exploration of their interconnections.